RELIABILITY ANALYSIS OF SECURITY CHECK POINT EQUIPMENT IN CHECKING PASSENGER LUGGAGE AT JUANDA INTERNATIONAL AIRPORT SURABAYA - Rifqi Lucky Anggoro (Sean Institute, 2023)
In accordance with SKEP/2765/XII/2010 regulations, all who will enter the airport area must be checked through the Security Check Point first. The problem is with the equipment used to check passenger goods through the Security Check Point. Adequate work equipment in suitable and properly maintained conditions will help smooth operations so that items that are prohibited or not allowed to enter the aircraft cabin do not escape. The research uses a qualitative descriptive method, arranged systematically from the results of interviews, observation and documentation. Research quality is research that is used to investigate, find, describe, and explain the quality of influences that cannot be explained, measured or described through a quantitative approach. Based on the results of the interviews and observations, it can be explained that the Security Check Point equipment must be checked regularly and recorded starting from the Aviation Security officer's report to the Airport Electronics officer. 4 X-ray equipment only 1 X-ray has problems so the inspection process is sometimes closed, 4 WalkTrough Metal Detector equipment is safely under control for inspection. In some HandHeld Metal Detector tools, problems often occur, the HandHeld Metal Detector report is not attached because if the sensor from the HandHeld Metal Detector equipment experiences problems, the equipment is immediately replaced with a new one.